PELVIC ROCKING EXERCISE PADA IBU BERSALIN TERHADAP LAMA WAKTU PERSALINAN - Ratna Ariesta Dwi Andriani; Ika Mardiyanti; Rizki Amalia (STIKES Cendekia Utama Kudus, 2022)
The results of Riskesdas (2018) in Central Java Province, the number of cases of complications of prolonged labor occupies the second highest number after complications of premature rupture of membranes, which is 5.2%. Given the high incidence of prolonged labor, it is necessary to do proper handling from a midwife. One of the efforts that can be done by midwives is to do pelvic rocking exercises for mothers in labor. The purpose of this study was to determine the effect of pelvic rocking exercise on the length of labor time. The research design used is an observational research type, with a Quasi Experiment design with a nonequivalent control group design. Then the data obtained were analyzed using the Mann Whitney test. The results of the study stated that the P-value was 0.000 <0.05, this means that there is a significant difference between the groups that do pelvic rocking exercise and those who do not do the length of time of delivery. The conclusion in this study is that there is an effect of pelvic rocking exercise on mothers giving birth to the length of time of delivery. This proves that pelvic rocking exercise is an activity that is quite effective in helping to accelerate the cervical opening process so that the labor process runs quickly.